Comparison of transitional vs surgical menopause on monoamine and amino acid levels in the rat brain. (15th November 2018) - Long, Tao; Yao, Jeffrey K.; Li, Junyi; Kirshner, Ziv Z.; Nelson, Doug; Dougherty, George G.; Gibbs, Robert B.
Abstract: Loss of ovarian function has important effects on neurotransmitter production and release with corresponding effects on cognitive performance. To date, there has been little direct comparison of the effects of surgical and transitional menopause on neurotransmitter pathways in the brain. In this study, effects on monoamines, monoamine metabolites, and the amino acids tryptophan (TRP) and tyrosine (TYR) were evaluated in adult ovariectomized (OVX) rats and in rats that underwent selective and gradual ovarian follicle depletion by daily injection of 4-vinylcyclohexene-diepoxide (VCD). Tissues from the hippocampus (HPC), frontal cortex (FCX), and striatum (STR) were dissected and analyzed at 1- and 6-weeks following OVX or VCD treatments. Tissues from gonadally intact rats were collected at proestrus and diestrus to represent neurochemical levels during natural states of high and low estrogens. In gonadally intact rats, higher levels of serotonin (5-HT) were detected at proestrus than at diestrus in the FCX. In addition, the ratio of 5-hydroxyindoleacetic acid (5-HIAA)/5HT in the FCX and HPC was lower at proestrus than at diestrus, suggesting an effect on 5-HT turnover in these regions. No other significant differences between proestrus and diestrus were observed. In OVX- and VCD-treated rats, changes were observed which were both brain region- and time point-dependent. In the HPC levels of norepinephrine, 5-HIAA, TRP and TYR were significantly reduced at 1 week, but not 6 weeks, in both OVX and VCD-treated rats relative to proestrus and diestrus. In the FCX, dopamine levels were elevated at 6 weeks after OVX relative to diestrus. A similar trend was observed at 1 week (but not 6 weeks) following VCD treatment. In the STR, norepinephrine levels were elevated at 1 week following OVX, and HVA levels were elevated at 1 week, but not 6 weeks, following VCD treatment, relative to proestrus and diestrus. Collectively, these data provide the first comprehensive analysis comparing the effects of two models of menopause on multiple neuroendocrine endpoints in the brain. These effects likely contribute to effects of surgical and transitional menopause on brain function and cognitive performance that have been reported. Highlights: Comparison of surgical vs. transitional menopause on neurochemical markers in the brain. Significant effects on serotoninergic, dopaminergic, and noradrenergic endpoints, and levels of amino acids, were detected. Effects were brain-region specific and time-dependent. Few differences between the two models on neurochemical endpoints were detected.